Main Plant Growth of Teak (Tectona grandis Linn F.) in Small Scale Private in Conggeang District, Sumedang Regency. - Asep Hendra Supriatna; Nurheni Wijayanto (Jurnal Silvikultur Tropika, 2011)
The need for teak wood processing in Indonesia is still high both for domestic demand and export wood demand. But the shortage of teak wood demand can give opportunities for people to cultivate teak on their privately land. The purpose of this research is to examine the main plant growth of teak (Tectona grandis Linn F.) in small scale private forest and compare it with teak’s growth from monoculture forest at Perum Perhutani KPH Sumedang in same ages. The main data of plant dimensional were taken with census method from teak plants in each of the selected land such as height, canopy diameter and canopy projection. In this research, soil parameter observed consist of physical and chemical content of soil  samples  from  each  selected  land  then  analyzed  in  laboratory.  Crown  closure  data  taken  by  using  a  spiracle     densiometer. The history of land management known by interview with farmers in each selected land. Those data were analyzed descriptively.            The results showed that the observed forest have 3 (three) different age classes of teak plantation. They are teak plant with  class  age  of  3  years,  6  years,  and  12  years  whom  the  growth  of  teak  are  different  in  those  parameter  such  as diameter, height, crown closure and basal area. Growth of teak plantation in the village of Babakan Asem is a plant with  the best teak growth among the other villages. Their growth maybe influenced by several factors, that is  the condition of the site or soil condition factors and cultivation activities. The result of crown closure show that the majority of sunlight blocked  by  the  crop  canopy  of  teak,  so  less  than  40%  of  sunlight  can  reach  the  soil  surface.  That  condition  maybe affected by size crop of teak and the distance between teak plantation it self. The result of soil analysis indicated that  physical and chemical soil content in Conggeang District are impact on teak growth which bulk density, water storage, KTK, pH, and other chemical substance are related to teak diameter’s  growth.             Growth  of  teak  plantation  between  small  scale  private forest  and  Perum  Perhutani  were  significantly different  in class  ages of  3 and 12 years  and didn’t  different  at  class ages of  6 years  in diameter.  The difference in  teak growth between  small  scale  private  forest  and  Perum  Perhutani  are  caused  by  a  factor  of  using  teak  seed  and  the  forest management.